MATHEMATICAL CRITICAL THINKING ABILITY OF MIDDLE SCHOOL STUDENTS THROUGH THE THINKING ALOUD PAIR PROBLEM SOLVING LEARNING MODEL - Darwani; Hafriani; Alya Karima (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
Indonesian students' critical thinking abilities are still relatively low, for this reason there is a need for solutions to improve students' critical mathematical thinking abilities. By using the Thinking Aloud Pair Problem Solving (TAPPS) learning model. The aim of this research is to see the increase in students' mathematical critical thinking skills by implementing the TAPPS learning model. This type of research is an experiment for one group with a Pretest-Posttest One-Group Design. The instruments in this research are Pretest and Posttest mathematical critical thinking skills and the supporting instruments are RPP and LKPD. The data obtained was tested and analyzed using Paired Sample T-Test. The results showed that the mathematical critical thinking abilities of class VIII-A students increased. The improvement was proven by statistical testing using the t-test with results showing that there was an increase in the mathematical critical thinking abilities of SMP/MTs students after the Thinking Aloud Pair Problem Solving learning model was implemented.